A Whole Cell Assay to Measure Caspase-6 Activity by Detecting Cleavage of Lamin A/C - Mintzer, Robert; Ramaswamy, Sreemathy; Shah, Kinjalkumar; Hannoush, Rami N.; Pozniak, Christine D.; Cohen, Frederick; Zhao, Xianrui; Plise, Emile; Lewcock, Joseph W.; Heise, Christopher E. (PLOS ONE, 2012)
Caspase-6 is a cysteinyl protease implicated in neurodegenerative conditions including Alzheimer's and Huntington's disease making it an attractive target for therapeutic intervention. A greater understanding of the role of caspase-6 in disease has been hampered by a lack of suitable cellular assays capable of specifically detecting caspase-6 activity in an intact cell environment. This is mainly due to the use of commercially available peptide substrates and inhibitors which lack the required specificity to facilitate development of this type of assay. We report here a 384-well whole-cell chemiluminescent ELISA assay that monitors the proteolytic degradation of endogenously expressed lamin A/C during the early stages of caspase-dependent apoptosis. The specificity of lamin A/C proteolysis by caspase-6 was demonstrated against recombinant caspase family members and further confirmed in genetic deletion studies. In the assay, plasma membrane integrity remained intact as assessed by release of lactate dehydrogenase from the intracellular environment and the exclusion of cell impermeable peptide inhibitors, despite the induction of an apoptotic state. The method described here is a robust tool to support drug discovery efforts targeting caspase-6 and is the first reported to specifically monitor endogenous caspase-6 activity in a cellular context.